2022
DOI: 10.1111/iju.15039
|View full text |Cite
|
Sign up to set email alerts
|

Association of financial toxicity with quality of life in testicular cancer survivors

Abstract: Objectives Most testicular cancer (TC) survivors have long‐term survival. However, the association between financial toxicity (FT), which is an economic side effect of cancer treatment, and the quality of life (QOL) of TC survivors is still unclear. Thus, the impact of FT on the QOL of TC survivors was examined in a multi‐institutional cross‐sectional study. Methods We recruited TC survivors from eight high‐volume institutions in Japan between January 2018 and March 2019. A total of 562 participants completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
3
12
1
Order By: Relevance
“…31 Measurement of FT using the financial difficulties item of the EORTC QLQ-C30 was previously used in other studies. 6,32,33…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Measurement of FT using the financial difficulties item of the EORTC QLQ-C30 was previously used in other studies. 6,32,33…”
Section: Methodsmentioning
confidence: 99%
“…31 Measurement of FT using the financial difficulties item of the EORTC QLQ-C30 was previously used in other studies. 6,32,33 HRQoL was evaluated using the functioning and symptoms scales and the global health status/QoL (GHS/QoL) scale of…”
Section: Assessment Of Ft and Hrqolmentioning
confidence: 99%
“…And each item was given on a Likert-type format with 5 options (1 = none of the time, 5 = all of the time). The total score ranges from 10 to 50, with the following stages: none (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), mild (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), moderate (30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and severe (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Wu and Jiang translated it into Chinese with satisfactory internal consistency coe cient (Cronbach's α = 0.91) [38].…”
Section: Self-perceived Burden Scale (Spbs)mentioning
confidence: 99%
“…10 Recently, a multi-institutional, cross-sectional study was conducted to evaluate health-related QOL and fertility among TC survivors using the EORTC QLQ-TC26 in Japan. 12,[18][19][20] The EORTC QLQ-TC26 includes the questionnaire about sexual functioning; erectile and ejaculatory functions. Therefore, we evaluated sexual function after treatment for TC using the EORTC QLQ-TC26 and analyzed the impact of treatment on sexual function among TC survivors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we reported that ejaculation disorders occurred at a high rate following RPLND, and TC survivors after RPLND showed lower sexual QOL in a single‐institutional study 10 . Recently, a multi‐institutional, cross‐sectional study was conducted to evaluate health‐related QOL and fertility among TC survivors using the EORTC QLQ‐TC26 in Japan 12,18–20 . The EORTC QLQ‐TC26 includes the questionnaire about sexual functioning; erectile and ejaculatory functions.…”
Section: Introductionmentioning
confidence: 99%